Dynamic Lycra® orthoses as an adjunct to arm rehabilitation after stroke: a single-blind, two-arm parallel group, randomized controlled feasibility trial. (August 2019) - Morris, Jacqui H; John, Alexandra; Wedderburn, Lucy; Rauchhaus, Petra; Donnan, Peter T
Objective: The aim of this study was to explore the feasibility of conducting a randomized controlled trial of dynamic Lycra ® orthoses as an adjunct to arm rehabilitation after stroke and to explore the magnitude and direction of change on arm outcomes. Design: This is a single-blind, two-arm parallel group, feasibility randomized controlled trial. Setting: In-patient rehabilitation. Subjects: The study participants were stroke survivors with arm hemiparesis two to four weeks after stroke receiving in-patient rehabilitation. Interventions: Participants were randomized 2:1 to wear Lycra ® gauntlets for eight hours daily for eight weeks, plus usual rehabilitation ( n  = 27), or to usual rehabilitation only ( n  = 16). Main measures: Recruitment, retention, fidelity, adverse events and completeness of data collection were examined at 8 and 16 weeks; arm function (activity limitation; Action Research Arm Test, Motor Activity Log) and impairment (Nine-hole Peg Test, Motricity Index, Modified Tardieu Scale). Structured interviews explored acceptability. Results: Of the target of 51, 43 (84%) participants were recruited. Retention at 8 weeks was 32 (79%) and 24 (56%) at 16 weeks. In total, 11 (52%) intervention group participants and 6 (50%) control group participants (odds ratio = 1.3, 95% confidence interval = 0.2 to 7.8) had improved Action Research Arm Test level by 8 weeks; at 16 weeks, this was 8 (61%) intervention and 6 (75.0%) control participants (odds ratio = 1.1, 95% confidence interval = 0.1 to 13.1). Change on other measures favoured control participants. Acceptability was influenced by 26 adverse reactions. Conclusion: Recruitment and retention were low, and adverse reactions were problematic. There were no indications of clinically relevant effects, but the small sample means definitive conclusions cannot be made. A definitive trial is not warranted without orthoses adaptation.